Synthesis, Characterization and Biological Study of Mixed Ligand Complexes Derived from Dithiocarbamate and Azo - Enaam I. Yousif (Journal of Global Pharma Technology, 2018)
The formation, structural characterisation of mixed ligand complexes of Co II, Zn II and Cd II metal ions with dithiocarbamate, azo and 1, 10-phenanthroline are reported. Ligands and complexes were characterised by analytical and spectroscopic analyses including; FTIR, electronic and 1H, 13C-NMR spectroscopy, microanalysis, chloride content, thermal analysis, magnetic susceptibility and conductance. Physico-chemical techniques indicated complexes demonstrated six coordinate structures in the solid and solution state. Biological activity of the prepared ligands and their mixed metal complexes were screened for their antimicrobial activity against four bacterial species ((Bacillus stubtilis and Staphylococcus aureus (G+)), Escherichia coli and Enterobacter (G-)). Biological data showed that complexes become potentially more active against these tested bacteria compared with the free ligandsKeywords: Mixed ligand complexes; Structural characterization; Thermal analysis; Biological activity.